THE EFFECTIVENESS OF HEALTH EDUCATION PEER EDUCATION METHOD USING AUDIO VISUAL MEDIA ON TEENAGERS' UNDERSTANDING OF SEX EDUCATION CLASS 11 SMAN 1 Boyolangu Tulungagung - Ria Anggraini; Berlian Yuli Saputri; Ketjuk Herminaju; Dewi Zuniawati (Jurnal Penelitian Sekolah Tinggi Ilmu Kesehatan Nahdlatul Ulama Tuban, 2023)
Free sex is one of the problems of lack of sex education and some of the problems that can result from casual sex in adolescents in the short term include KTD (unwanted pregnancy), abortion, and STDs (Sexually transmitted diseases). This study was conducted from February 20 until March 20, 2023, and aims to see the Effectiveness of Health Education Peer Education Method with Audio Visual Media on Adolescent Understanding of ''Sex Education'' Grade 11 SMAN 1 Boyolangu Tulungagung in 2023. The research design used in this study quasy experimental with Non-equivalent Control Group Design (Pretest Posttest) The population in this study was all grade XI students of  SMAN 1 Boyolangu. While the number of research samples was 82 respondents selected using the Purposive Sampling method. Data processing in the form of editing, coding, tabulating, cleaning, and then analyzing data using non-parametric Wilcoxon sign rank test & Mann – Whitney. From the Wilcoxon Test, both methods show that a significant value p = 0.000 < a (0.05), so H1 is accepted meaning that there is an Effect of Health Counseling. From the results of the Mann - Whitney Test, the Mean Rank of the Peer Education method was obtained with a value of 35.43. And the Mean Rank of the audio-visual method with a value of 47.57. It is known that the Mean Rank of the Audio Visual Method is higher than the Peer Education method. The Mann-Whitney test shows a significance value of p= 0.019. So that H1 is accepted, which means that there is an Effectiveness of Health Counseling with Peer Education and Audio Visual Methods. It can be concluded that the audio-visual method is more effective as a means of health counseling on the understanding of sex education in grade 11 adolescents at SMAN 1 Boyolangu Tulungagung in 2023. For this reason, the audio-visual method is recommended for health counseling to increase adolescent understanding of Sex Education.  Keywords: Free Sex; Health Education; Tee